Development of a general bioluminescent activity assay for peptide ligases. (9th March 2022) - Zhang, Cong‐Hui; Shao, Xiao‐Xia; Wang, Xin‐Bo; Shou, Li‐Li; Liu, Ya‐Li; Xu, Zeng‐Guang; Guo, Zhan‐Yun
Abstract : In recent years, some peptide ligases have been identified, such as bacterial sortases and certain plant asparaginyl or prolyl endopeptidases. Peptide ligases have wide applications in protein labelling and cyclic peptide synthesis. To characterize various known peptide ligases or identify new ones, we propose a general bioluminescent activity assay via the genetic fusion of a recognition motif of peptide ligase(s) to the C‐terminus of an inactive large NanoLuc fragment (LgBiT) and the chemical introduction of a nucleophilic motif preferred by the peptide ligase(s) to the N‐terminus of the low‐affinity SmBiT complementation tag. After the inactive ligation version LgBiT protein was ligated with the low‐affinity ligation version SmBiT tag by the expected peptide ligase(s), its luciferase activity would be restored and could be quantified sensitively according to the measured bioluminescence. In the present study, we first validated the bioluminescent activity assay using bacterial sortase A and plant‐derived butelase‐1. Subsequently, we screened novel peptide ligases from crude extracts of selected plants using two LgBiT‐SmBiT ligation pairs. Among 80 common higher plants, we identified that five of them likely express asparaginyl endopeptidase‐type peptide ligase and four of them likely express prolyl endopeptidase‐type peptide ligase, suggesting that peptide ligases are not so rare in higher plants and more of them await discovery. The present bioluminescent activity assay is ultrasensitive, convenient for use, and resistant to protease interference, and thus would have wide applications for characterizing known peptide ligases or screening new ones from various sources in future studies. Abstract : A general bioluminescent activity assay suitable for various peptide ligases was developed based on the inactive large NanoLuc fragment (LgBiT) and the low‐affinity SmBiT complementation tag. The assay is ultrasensitive, convenient for use, and resistant to protease interference, thus would have wide applications for characterizing known peptide ligases or screening new ones from various sources in future studies.